The potential of participatory science data for modelling wildlife habitat selection in a rapidly urbanising area - Jade Simoen; Gabriella R. M. Leighton; Zoë A. Woodgate; Laurel E. K. Serieys; Deborah Wettlaufer; Jacqueline M. Bishop (Urban Ecosystems, 2026)
Increasing urbanisation challenges biodiversity conservation, especially for wildlife adapting to fragmenting habitats. Carnivores are particularly affected, due to their large spatial needs and low densities. Solitary felids are particularly cryptic and detecting them is challenging; traditional methods often face financial and logistical constraints necessitating alternative approaches for species monitoring. Participatory science (PS) may offer a cost-effective, scalable solution; however, spatial bias, non-representative observations, and observer expertise remain concerns. This study assessed PS data reliability and applicability for modelling caracal ( Caracal caracal ) habitat selection within the rapidly urbanising Cape Peninsula of Cape Town, South Africa. We compared location data from PS ( n = 897) and GPS collars ( n = 14,253) using a framework to conduct a systematic assessment of spatial and temporal coverage, aptness, and application of the datasets. Resource selection functions for both datasets were evaluated for directionality, significance, and standard error to compare output similarity. Results showed general agreement between models for key habitat variables (e.g., distance to urban edge, roads, and vegetation greenness), suggesting that PS in cities is a useful complementary method to provide valuable longer-term ecological insights into habitat use by adaptable urban wildlife. While GPS telemetry captured finer-scale movement in our study system, PS data offered broader temporal and sufficient spatial coverage. Our assessment highlights both strengths and limitations of crowdsourced occurrence data, emphasising PS’s potential in urban carnivore ecology research when data limitations are carefully considered.

Major Fusarium species and mycotoxins associated with freshly harvested maize grain in Uruguay - A. del Palacio; B. Corallo; M. Simoens; Jacqueline Cea; I. de Aurrecoechea; I. Martinez; A. Sanchez; S. Stewart; D. Pan (Mycotoxin Research, 2023)

Valorization of coffee byproducts for bioethanol production using lignocellulosic yeast fermentation and pervaporation - D. Dadi; A. Beyene; K. Simoens; J. Soares; M. M. Demeke; J. M. Thevelein; K. Bernaerts; P. Luis; B. Van der Bruggen (International Journal of Environmental Science and Technology, 2018)

Spatially based methods to assess the ecological status of riverine fish assemblages in European ecoregions - S. SCHMUTZ; A. MELCHER; C. FRANGEZ; G. HAIDVOGL; U. BEIER; J. BÖHMER; J. BREINE; I. SIMOENS; N. CAIOLA; A. DE SOSTOA; M. T. FERREIRA; J. OLIVEIRA; et al. (Fisheries Management and Ecology, 2007)
The objective was to develop spatially based (type‐specific) methods to assess the ecological status of European rivers according to the EU Water Framework Directive. Some 15 000 samples from about 8000 sites were pre‐classified within a five‐tiered classification system based on hydromorphological and physico‐chemical pressures. The pre‐classification was used to identify reference conditions and to calibrate the assessment methods. Clustering reference sites based on relative species composition resulted in 60 fish assemblage types within 11 of the ecoregions under study. Discriminant function analyses (DFAs) were employed to identify environmental parameters characterising fish assemblage types; altitude, river slope, wetted width, mean air temperature and distance from source were the principal predictors. These environmental parameters were used to assign impacted sites with altered fish assemblage composition to the reference fish assemblage type. Metrics (fish assemblage descriptors) responding to human pressures were selected based on correlation and DFAs. Assessment methods were developed for 43 fish assemblage types. Metrics based on individual sentinel species were more often used in type‐specific methods than metrics related to reproduction, habitat and feeding. Metrics based on long‐distance migrants and potamodromous species were more sensitive to human pressures than overall composition metrics, e.g. total number of species. Only some of the tested metrics showed pressure‐specific responses, i.e. reacted to one type of pressure but not to others. Insectivorous, intolerant and lithophilic species exclusively responded (decreased) to chemical and hydromorphological pressures in 14–19%. Omnivorous species was the only metric type that showed a consistent reaction (increase) to continuum disruptions in 25% of the cases. Accuracy of methods based on cross‐validation with pre‐classification varied between 47% and 98% (mean 81%) when contrasting calibration data set (class 1 and 2) with degraded sites (class 3, 4 and 5).